Gender Equality dan Urgensinya Bagi Ketahanan Keluarga di Kecamatan Bangsri Jepara - Lutviani Lutviani (Isti`dal : Jurnal Studi Hukum Islam, 2022)
This research was motivated by; First, the implementation of PPPA Ministerial Regulation Number 6 of 2013 concerning the Implementation of Family Development Article 3, letter (a) concerning the Foundation of Legality and Family Integrity which is more specific on the Gender Partnership indicator and its Urgency in Forming Family Resilience. Second, the facts related to the growth in the number of women's workforce which is higher than that of men and indications of weak family resilience are evidenced by the high divorce rate in Jepara district. And third, data that mentions Bangsri Jepara District as the District that has the highest divorce rate in Jepara during the last two years (2020-2022). This research is intended to determine the quality of understanding and application of understanding Gender Equality in Bangsri District families. The result of this research is that the understanding of gender equality has not been fully practiced. And this concept is very urgent for efforts to strengthen family resilience.Penelitian ini dilatar belakangi oleh; Pertama, Implementasi Peraturan Menteri PPPA Nomor 6 Tahun 2013 tentang Pelaksanaan Pembangunan Keluarga Pasal 3, huruf (a) tentang Landasan Legalitas dan Keutuhan Keluarga yang lebih dispesifikkan pada indikator Kemitraan Gender dan Urgensinya dalam Pembentukan Ketahanan Keluarga. Kedua, Fakta terkait pertumbuhan jumlah angkatan kerja perempuan yang lebih tinggi dari pada laki-laki dan indikasi ketahanan keluarga yang lemah dibuktikan dengan angka perceraian tinggi di kabupaten Jepara. Dan Ketiga, data yang menyebutkan Kecamatan Bangsri Jepara sebagai Kecamatan yang memiliki angka perceraian paling tinggi di Jepara selama kurun waktu dua tahun terakhir (2020-2022). Penelitian ini dimaksudkan untuk mengetahui kualitas pemahaman dan penerapan pemahaman Gender Equality di keluarga Kecamatan Bangsri. Hasil dari penelitian ini adalah bahwa pemahaman gender equality belum sepenuhnya dipraktikkan. Dan konsep tersebut sangat urgen untuk upaya menguatkan ketahanan keluarga.